Fair trade or trade fair? International food trade and cross-border macronutrient flows. (August 2020) - Traverso, Silvio; Schiavo, Stefano
Highlights: The quantity of macronutrients traded internationally has more than doubled since 1996. Proteins are the most expensive macronutrient, followed by lipids and carbohydrates. International food trade enhances the availability of macronutrients in low-income countries. International food trade improves low-income countries' aggregate food access. Abstract: This study examines global food trade from a nutritional perspective, paying particular attention to its implications for food security in low-income countries. By describing food trade in terms of the quantities of three essential macronutrients (carbohydrates, lipids, and proteins) embedded in food, the analysis goes beyond a simple description of trade values, quantities, or caloric content, as is common in the literature. Furthermore, the study provides estimates of the implicit price of each macronutrient, their evolution over time, and their implications in terms of North-South food trade. The data show that, over the 1996–2014 period, the volume of macronutrients exchanged on international markets has more than doubled, with carbohydrates accounting for over 60% of trade flows, but proteins and lipids growing at a faster pace. Proteins were found to be the most expensive macronutrient, followed by lipids and carbohydrates. In general, macronutrients embedded in animal and processed products are more expensive than those in vegetal and unprocessed food. The results also suggest that the participation in international food trade has positive effects on low-income countries' aggregate food availability and food access, two pillars of food security. Indeed, low-income countries register a net inflow of all macronutrients and take advantage of "nutritional arbitrages" available on international food markets due to macronutrients' price differentials.